“Home Away from Home”? How International Students Handle Difficult and Negative Experiences in American Higher Education - Yan, Lu (Wendy); Pei, Shaohua (Linda) (Journal of International Students, 2018)
International students attending American universities often receive confusing messages: on one hand, for their contribution to the U.S. economy and fostering of domestic students’ multicultural awareness; on the other, they are often targets of hostility and bias on and off campus. This qualitative phenomenological study examined 12 international students’ perceptions of difficult and negative experiences in the context of American culture and a reputedly friendly Midwestern university. Four major themes emerged: (a) their on-campus experiences; (b) the off-campus experiences; (c) their reasons for unpleasant experiences, and (d) their suggestions for professors and peers to be more inclusive. Besides these students’ struggles with administrators, faculty, and domestic students, their off-campus challenges sometimes dimmed their hopes for truly having a “home away from home.”